2015
DOI: 10.1007/s11481-015-9608-y
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumor Activity of Plant-Derived Non-Psychoactive Cannabinoids

Abstract: As a therapeutic agent, most people are familiar with the palliative effects of the primary psychoactive constituent of Cannabis sativa (CS), Δ9-tetrahydrocannabinol (THC), a molecule active at both the cannabinoid 1 (CB1) and cannabinoid 2 (CB2) receptor subtypes. Through the activation primarily of CB1 receptors in the central nervous system, THC can reduce nausea, emesis and pain in cancer patients undergoing chemotherapy. During the last decade, however, several studies have now shown that CB1 and CB2 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 103 publications
(150 reference statements)
2
78
0
4
Order By: Relevance
“…548), and in vivo in the presence of a PPAR␥ antagonist (713). Furthermore, CBD is able to inhibit cancer cell invasion and metastasis (478,548,715).…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…548), and in vivo in the presence of a PPAR␥ antagonist (713). Furthermore, CBD is able to inhibit cancer cell invasion and metastasis (478,548,715).…”
Section: Cancermentioning
confidence: 99%
“…548), and in vivo in the presence of a PPAR␥ antagonist (713). Furthermore, CBD is able to inhibit cancer cell invasion and metastasis (478,548,715). These actions, in highly aggressive human breast cancer cells, are in part mediated by inhibition of epidermal growth factor (EGF), NF-B, ERK/AKT, and matrix metalloproteinase 2 and 9 signaling pathways (238).…”
Section: Cancermentioning
confidence: 99%
“…Other studies have shown the ability of cannabinoids to affect cellular signalling pathway/s essential for cell survival and growth Kogan, 2005). Some studies have also demonstrated and suggested the involvement of autophagy in the mechanism of cannabinoidinduced cytotoxicity (Armstrong et al 2015;Vara et al, 2011;McAllister et al, 2015).…”
Section: Anti-tumour Effects Of Cannabinoidsmentioning
confidence: 99%
“…The non-psychoactive nature of cannabidiol (CBD), has prompted many studies, both in vivo and in vitro , that support a role for CBD in tumor regression and inhibition of cell viability through reactive oxygen species (ROS)-driven and caspase-dependent apoptosis (reviewed by McAllister et al, 2015). However, the anti-cancer potential of CBD has not been translated into the clinic.…”
Section: Introductionmentioning
confidence: 99%